Production and first-in-man use of T cells engineered to express a HSVTK-CD34 sort-suicide gene. - Hong Zhan (PLoS ONE, 2013)
UNLABELLED:Suicide gene modified donor T cells can improve immune reconstitution after allogeneic haematopoietic stem cell transplantation (SCT), but can be eliminated in the event of graft versus host disease (GVHD) through the administration of prodrug. Here we report the production and first-in-man use of mismatched donor T cells modified with a gamma-retroviral vector expressing a herpes simplex thymidine kinase (HSVTK):truncated CD34 (tCD34) suicide gene/magnetic selection marker protein. A stable packaging cell line was established to produce clinical grade vector pseudotyped with the Gibbon Ape Leukaemia Virus (GALV). T cells were transduced in a closed bag system following activation with anti-CD3/CD28 beads, and enriched on the basis of CD34 expression. Engineered cells were administered in two escalating doses to three children receiving T-depleted, CD34 stem cell selected, mismatched allogeneic grafts. All patients had pre-existing viral infections and received chemotherapy conditioning without serotherapy. In all three subjects cell therapy was tolerated without acute toxicity or the development of acute GVHD. Circulating gene modified T cells were detectable by flow cytometry and by molecular tracking in all three subjects. There was resolution of virus infections, concordant with detectable antigen-specific T cell responses and gene modified cells persisted for over 12 months. These findings highlight the suitability of tCD34 as a GMP compliant selection marker and demonstrate the feasibility, safety and immunological potential of HSVTK-tCD34 suicide gene modified donor T cells. TRIAL REGISTRATION:ClinicalTrials.gov NCT01204502 <NCT01204502>